The morphology of spatial composition hierarchy for Kutai House / Mohd Khazli Aswad Khalid ... [et al.] - Mohd Khazli Aswad Khalid, Mohd Khazli Aswad; Ahmad Zawawi, Zuraihana; Hashim, Hasnan; Abdullah Salleh, Alia; Zahari, Nurul Fadzila (2022)
The purpose of this article is to find out how morphology affects the spatial hierarchical transformation of Kutai House. The main problem of spatial morphological change occurs due to several factors human behaviour and community social for space using. The objectives of this research are, to determine the spatial layout and analysis the factors and analyse of morphology affects the spatial hierarchical transformation for Kutai House. The method used is descriptive analysis and exposed to the results of field investigations. The result obtained from this research is the change of the internal spatial hierarchy of Kutai houses. The spatial hierarchy of traditional Malay houses can be determined from the public space, then space, semi-public, semi-private, and private space. The Kutai house was selected as a case study, using quantitative methods to assign the components of space found in Malay houses to determine the nature, function, and morphology change of space. At the end of the study, the spatial hierarchy of traditional Malay houses can be determined from the public space, and then space, semi-public, semi-private, and private space can be determined. The transition space from semi-public to semi-private indicates a change in the social interaction between residents and guests, the morphology of the space occurs to meet the needs of privacy at home and social relationships outside. The impact of spatial morphology for this research is the main result for the further study.